Core‐Shell Nanoparticles with a Redox Polymer Core and a Silica Porous Shell as High‐Performance Cathode Material for Lithium‐Ion Batteries. Issue 3 (13th November 2019) - Jia, He; Friebe, Christian; Schubert, Ulrich S.; Zhang, Xiaozhe; Quan, Ting; Lu, Yan; Gohy, Jean-François
Abstract : A facile and novel method for the fabrication of core‐shell nanoparticles (PTMA@SiO2 ) based on a poly(2, 2, 6, 6‐tetramethylpiperidinyloxy‐4‐yl methacrylate) (PTMA) core and a porous SiO2 shell is reported. The core‐shell nanoparticles are further self‐assembled with negatively charged multi‐walled carbon nanotubes (MWCNTs), which results in the formation of a free‐standing cathode electrode. The porous SiO2 shell not only effectively improves the stability of the linear PTMA redox polymer with low molar mass in organic electrolytes but also leads to the uniform dispersion of PTMA active units in the MWCNTs conductive network. The PTMA@SiO2 @MWCNT composite electrode exhibits a specific capacity as high as 73.8 mAh g at 1 C and only 0.11% capacity loss per cycle at a rate of 2 C. Abstract : This study discloses the fabrication of nanoparticles made of redox polymer cores surrounded by stabilizing porous silica shells, that are dispersed in a conductive net work of multi‐walled carbon nanotubes. Because of their well‐controlled morphology, the resulting composite electrodes exhibit a high specific capacity and a long cycling life.